Introduction to species digests - Doran, J.C.; Turnbull, J.W.; Martensz, P.N.; Thomson, L.A.J.; Hall, N. (1997)
The volume is designed to provide a reference text for all those concerned with selecting and growing trees and shrubs in rural areas of developing countries and in the more tropical parts of Australia. This introduction to the species’ digests which follow describes the criteria used to select species to be included in the digests. The species described are those judged by a group of experienced botanists and forests as having the potential to provide fuelwood, fodder, posts, poles, shade and shelter, ground cover, or other desirable products and influences, as well as some selected specifically for their human food value. Each of 112 major species is illustrated with a colour photograph, a distribution map showing its natural occurrence and is supplemented by detailed information on botanical features, natural occurrence, ecological conditions, utilisation, silvicultural features, pests and diseases, limitations and related species. An extensive table is provided which lists described species and summarises their more important characteristics and uses. Characteristics included are environment (climate and soil), tree habit and uses (timber and non-timber).